2020
DOI: 10.1007/s11605-019-04331-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Sphincter Augmentation and Postoperative Dysphagia: Characterization, Clinical Risk Factors, and Management

Abstract: Introduction Magnetic sphincter augmentation (MSA) results in less severe side effects compared with Nissen fundoplication, but dysphagia remains the most common side effect reported by patients after MSA. This study aimed to characterize and review the management of postoperative dysphagia and identify the preoperative factors that predict persistent dysphagia after MSA. Material and Methods This is a retrospective review of prospectively collected data of patients who underwent MSA between 2013 and 2018. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 23 publications
5
85
3
Order By: Relevance
“…The attractive force between closed beads is roughly 40 g and exponentially decreases to 7g at full separation. A fibrous capsule will encase the MSA device in the weeks to months following surgery, adding another variable to its resistive potential(33,34). The data in the present study supports that the circumferential nature of MSA is superior to partial fundoplication while limiting the side-effects of Nissen fundoplication.One key feature which separates antireflux potential of Nissen fundoplication from Toupet fundoplication and MSA is the relative contributions native GEJ.…”
supporting
confidence: 73%
“…The attractive force between closed beads is roughly 40 g and exponentially decreases to 7g at full separation. A fibrous capsule will encase the MSA device in the weeks to months following surgery, adding another variable to its resistive potential(33,34). The data in the present study supports that the circumferential nature of MSA is superior to partial fundoplication while limiting the side-effects of Nissen fundoplication.One key feature which separates antireflux potential of Nissen fundoplication from Toupet fundoplication and MSA is the relative contributions native GEJ.…”
supporting
confidence: 73%
“…It should be noted that, during the study period, the sizer instrument has been replaced with a more user-friendly device in an attempt to improve the reproducibility of measurements. Furthermore, it has become clear over time that it is wiser to oversize by increasing 3 beads from the point of sizer release, and to use a larger MSA device to minimize dysphagia and decrease the likelihood of removal 19,20 . In our cohort of patients followed for 6-12 years, the overall estimated probability of MSA explant was 0.1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, our group reported that the change in sizing protocol, in addition to introduction of postoperative diet modification and avoiding early dilation, results in decreases in the dysphagia rate and need for dilation. 34 Although the clinical benefits of MSA are well established, the cost associated with the device has been perceived as a drawback by payers and this has slowed the widespread dissemination of this technique. A recent study by our group examined the economic impact of introducing MSA for the primary treatment of GERD.…”
Section: Discussionmentioning
confidence: 99%